1981
DOI: 10.1128/jb.147.2.326-332.1981
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic membrane fraction that promotes septation in an Escherichia coli lon mutant

Abstract: A particulate fraction derived from bacterial cells stimulates septation in irradiated Escherichia coli lon mutants when added to postirradiation plating media. It was established that the particles are derived from the cytoplasmic membrane and that they have been partially purified by sucrose density gradient centrifugation. These particles also contain the cytochrome-based respiratory activity of the cell. A variety of experiments established a correlation between the septation-promoting activity of the part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Microbial Membrane Fraction. A detailed procedure for the production of the oxygen-reducing membranes has already been published (Adler et al, 1981). Such membranes are now available as "Oxyrase" from Oxyrase, Inc., Box 899, Ashland, OH 44805.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial Membrane Fraction. A detailed procedure for the production of the oxygen-reducing membranes has already been published (Adler et al, 1981). Such membranes are now available as "Oxyrase" from Oxyrase, Inc., Box 899, Ashland, OH 44805.…”
Section: Methodsmentioning
confidence: 99%
“…It has been previously reported that a partially purified membrane fraction from Escherichia coli contains an active electron transport system that can efficiently reduce dissolved oxygen to water in various fermentation media in the presence of a mild hydrogen donor such as sodium lactate, therefore enabling the manipulation of many anaerobic strains (Adler and Crow, 1981;Adler et al, 1983). The sterile membrane fragments can be used without foaming problems, and they have no inhibitory effects on the growth of bacteria, even when they are present in 10-fold excess concentration (Adler and Crow, 1981). A further advantage of the membrane fraction is that, as an enzymatic system, it can be used continuously (assuming that the necessary lactate concentration is present in the medium).…”
Section: Introductionmentioning
confidence: 99%
“…Cell-free extracts of NAG-grown secondary bacteria were prepared as described by Adler et al [12], however, rupture of the cells was achieved by sonication under an atmosphere of N,. The extracts were filter-sterilized (0.2 ffm), kept under an atmosphere of N~ and frozen (-20°C) until needed.…”
Section: Preparation Of Cell-free Extracts and Membrane Fractionsmentioning
confidence: 99%
“…The rate of dissolved oxygen removal is highly pH dependent, with a maximum activity at pH 8.4 and 55˚C [38]. Other uses of Oxyrase include growing anaerobic cells, increasing cell growth in the log phase, increasing maximum titer and protecting certain biomolecules from reactions with oxygen [37,39].…”
Section: Introductionmentioning
confidence: 99%